La relazione tra ruolo imprenditoriale e piccole aziende ad alto potenziale - Passaro, Renato; Thomas, Antonio (Piccola Impresa / Small Business, 2007)
This paper is addressed to discuss about the subjective characteristics of entrepreneurs that allow them to start or to run small firms able to contribute in a stable and relevant manner to the local development (high-potential firms). For this purpose a literature analysis and a field research based on a sample of 101 small firms have been conducted. This topic is discussed with reference to a backward area context which is also characterized by the presence of many policy measures aimed to directly support small business. Some policy measures indication emerge, that address the necessity to propose innovative instruments aimed to reinforce and to support, in a business management perspective, the entrepreneurial role in order to sustain the economic development.